A numerical study on the seismic response of a geosynthetic reinforced soil slope - Castorina Silva Vieira (2007)
In this work the two-dimensional finite difference program Fast Lagrangian Analysis of Continua (FLAC) was used to model the seismic response of a geosynthetic reinforced steep slope. The paper presents a study that was carried out to analyze the influence of boundary conditions and input motion. The permanent displacements of the slope face and reinforcement tensile forces are analyzed and compared. (c) CIMNE, 2007.